If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4y + 4 = -2(4y + 14) Reorder the terms: 4 + -4y = -2(4y + 14) Reorder the terms: 4 + -4y = -2(14 + 4y) 4 + -4y = (14 * -2 + 4y * -2) 4 + -4y = (-28 + -8y) Solving 4 + -4y = -28 + -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. 4 + -4y + 8y = -28 + -8y + 8y Combine like terms: -4y + 8y = 4y 4 + 4y = -28 + -8y + 8y Combine like terms: -8y + 8y = 0 4 + 4y = -28 + 0 4 + 4y = -28 Add '-4' to each side of the equation. 4 + -4 + 4y = -28 + -4 Combine like terms: 4 + -4 = 0 0 + 4y = -28 + -4 4y = -28 + -4 Combine like terms: -28 + -4 = -32 4y = -32 Divide each side by '4'. y = -8 Simplifying y = -8
| k(t)=T^6+3t^4-46t^2+72 | | -7+3x=3x-7 | | 5r-9(2)=2 | | 44=x+18 | | 12y+6(-.5-2y)=-3 | | 1.2x+3.2=13 | | -2(-.5-2y)-4y=1 | | 16=X^2 | | 7y^2-12Y+5=0 | | 8(0)+6x=-4 | | -3(-0.6666666667+-1.333333333y)-4y=2 | | x^6+19x^3-216=0 | | 9x+7(-3x-5)=-43-4x | | 8y+6x=-4 | | (x+1)(3x^2-12)=0 | | -3x-4(-0.5+-0.75x)=2 | | y-12=7 | | 5x^2-19x+18= | | 2x+5(2-1x)=10 | | 7(3w+1)-9(1+2w)=-2(w+4)-(4w-5)+6 | | 1=x+.333x | | -9a^2-5a^2=0 | | y=2-5+-2.5y | | x+2(1.5)=4 | | 9(4-2y)-4y=3 | | -5s=24 | | -3p=72 | | y^2-3y+9=0 | | -2(-0.5-2y)-4y=1 | | 6v^2-3v-15=-2v | | 5.1(x-2)=1.02 | | 12y+6x=-3 |